A historical study of American patients with anti-neutrophil cytoplasmic antibody negative pauci-immune glomerulonephritis. Issue 4 (April 2016) - Shah, Shivani; Havill, John; Rahman, M.; Geetha, Duvuru
Abstract Anti-neutrophil cytoplasmic antibodies (ANCA) play an important role in the pathogenesis of ANCA-associated vasculitis. The lack of ANCA antibodies may indicate a variation in clinical presentation and outcomes of this disease. We identified 74 adult patients between 1995 and 2009 with the diagnosis of pauci-immune glomerulonephritis. Demographics, histological features, and treatment outcomes were compared between ANCA-positive and ANCA-negative patients. These factors were correlated with renal function at presentation and follow-up. Of the 74 patients, 57 were ANCA-positive, and 17 were ANCA-negative. Demographics and mean Birmingham Vasculitis Activity Score were similar between ANCA-negative and ANCA-positive patients at presentation. Renal function was significantly worse at presentation in the ANCA-negative patients (eGFR 16.59 vs. 31.89 ml/min/1.73 m2, p  = 0.03). Patients in the ANCA-negative group had a significantly higher interstitial fibrosis score compared to the ANCA-positive group (2.1 vs.1.6, p  = 0.04). The median time to remission was shorter in the ANCA-negative patients (51 vs. 78 days, p  = 0.01). Long-term renal function and 1-year patient and renal survival were similar between ANCA-negative and ANCA-positive patients. Baseline eGFR, percentage of normal glomeruli, glomerular sclerosis, and tubulointerstitial scarring predicted eGFR at 1 year in both groups similarly. This is the first historical review of American patients with pauci-immune glomerulonephritis, comparing patients with ANCA-negative and ANCA-positive serology. Although ANCA-negative patients present with lower eGFR and more interstitial fibrosis, 1-year and long-term outcomes in both groups are similar.